TRANSFORMASI PENDIDIKAN KEWARGANEGARAAN SEBAGAI PENDIDIKAN HUKUM - Zakki Abdillah Sjam; Deni Zein Tarsidi; Delila Kania (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2022)
To make Civic Education learning more functional, it is best to change the paradigm of Civic Education, which was originally a teaching program and transfer of civic knowledge to a means of legal Education. Civic education learning is felt to be less than optimal because the concept of Civic education learning is just a delivery of information from teachers to students, and students only memorize material instead of interpreting and understanding the content of the material, so it's time for the paradigm to be changed to maximize the function of Civic Education. This study uses a qualitative method with a literature study design, namely activities to collect information relevant to the topic or problem that is the object of the research. Implementing Legal Education in Civic Education is one of the efforts to create law-abiding citizens so that they can carry out their rights and obligations as citizens. This condition is very relevant to what is the goal of Civic Education. So Legal Education in Civic Education is an effort to achieve the goals of Civic Education. Legal Education is not limited to Legal Education which prepares professionals to build a national system. For this reason, Education, especially Civic Education, must be developed within the framework of legal awareness, both in formal and non-formal Education..